Impact of Selected Macroeconomics Variables on Sensex - Joseph K., Dr. Siby; T Thomas, Jerin (International Journal of Scientific Research and Management (IJSRM), 2022)
The macroeconomic variables are crucial for any change in the economy of a country. It is strongly believed that, fluctuations in macroeconomic variables will have impact on the returns of stock. Any changes among these variables have impact on the economy in various ways. The aim of the study was to determine the impact of selected economic variables namely Index of Industrial production (IIP), Consumer Price Index (CPI),  Crude Oil Prices (CO), Gold Price (GP) on Sensex  in India. The data from 1st January 2013 to December 2019 were used for this specific study. Linear regression analysis was carried out to understand the effect of macroeconomic variables on Sensex. A granger causality test was applied on the data to understand the possible impact of macroeconomic variables on stock prices. The findings of the study revealed that, out of the four variables; Gold price, CPI, Crude oil price is relatively more significant and likely to influence Indian stock market. The study reveals that , the presence of long run relation between the Sensex and select macroeconomic indicators and the Indian stock market is more driven by domestic macroeconomic factors.